Combined Untargeted and Targeted Fingerprinting by Comprehensive Two-Dimensional Gas Chromatography to Track Compositional Changes on Hazelnut Primary Metabolome during Roasting - Marta Cialiè Rosso; Federico Stilo; Carlo Bicchi; Melanie Charron; Ginevra Rosso; Roberto Menta; Stephen E. Reichenbach; Christoph H. Weinert; Carina I. Mack; Sabine E. Kulling; Chiara Cordero (Applied Sciences, 2021)
This study focuses on the detectable metabolome of high-quality raw hazelnuts (Corylus avellana L.) and on its changes after dry-roasting. Informative fingerprinting was obtained by comprehensive two-dimensional gas chromatography with fast-scanning quadrupole mass spectrometry (GC×GC-qMS) combined with dedicated data processing. In particular, combined untargeted and targeted (UT) fingerprinting, based on pattern recognition by template matching, is applied to chromatograms from raw and roasted samples of Tonda Gentile Trilobata and Anakliuri hazelnuts harvested in Italy and Georgia. Lab-scale roasting was designed to develop a desirable organoleptic profile matching industrial standards. Results, based on 430 peak features, reveal that phenotype expression is markedly correlated to cultivar and pedoclimatic conditions. Discriminant components between cultivars are amino acids (valine, alanine, glycine, and proline); organic acids (citric, aspartic, malic, gluconic, threonic, and 4-aminobutanoic acids); and sugars and polyols (maltose, xylulose, xylitol, turanose, mannitol, scyllo-inositol, and pinitol). Of these, alanine, glycine, and proline have a high informational role as precursors of 2-acetyl- and 2-propionylpyrroline, two key-aroma compounds of roasted hazelnuts. Roasting has a decisive impact on metabolite patterns—it caused a marked decrease (−90%) of alanine, proline, leucine and valine, and aspartic and pyroglutamic acid and a −50% reduction of saccharose and galactose.